Implementasi Pelatihan Guna Meningkatkan Kinerja Pegawai Desa Tanjugwangi - Apriani, Herni; Maryono, Dicky (STIM-LPI Makassar, 2024)
Human resources are a very important factor that cannot be separated from an organization, be it a government agency or a company. Training is the process by which new and existing employees acquire the skills they need to do their jobs. And Performance is emphasizing that employees are considered as a workforce that improves quality products and services. This research aims to find out why it is necessary to hold training in Tanjungwangi Village and to find out the implementation of employee training to improve the performance of Tanjungwangi Village employees. This type of research is descriptive qualitative. The method used in this research is the interview method. The results of this research show that the training organized by Tanjungwangi Village is only limited to computer training, so that employees in the village have to rely on their independent abilities to support their work. However, the increase in employee performance in Tanjungwangi Village is not only caused by internal training in the village itself, but is also influenced by various technical guidance (bimtek) provided by the government at the sub-district, district and provincial levels. So, collaboration between internal village training and technical guidance provided by the government outside the village is important to improve employee performance in Tanjungwangi Village.